Republic of Moldova : Third Reviews under the Extended Credit Facility and Extended Fund Facility Arrangements and Request for Modification of Performance Criteria. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
The economy strengthened in 2017. Higher-than-expected GDP growth was driven by strong domestic demand and a positive external environment. Inflation slowed, driven by regulated and food prices, prudent policies and exchange rate appreciation, to below the target of the National Bank of Moldova (NBM).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet